Emissions of VOCs, SVOCs, and mold during the construction process: Contribution to indoor air quality and future occupants' exposure. (4th February 2020) - Gallon, Victoria; Le Cann, Pierre; Sanchez, Mariangel; Dematteo, Charline; Le Bot, Barbara
Abstract: Building materials and human activities are important sources of contamination indoors, but little information is available regarding contamination during construction process which could persist during the whole life of buildings. In this study, six construction stages on two construction sites were investigated regarding the emissions of 43 volatile organic compounds (VOCs), 46 semi‐volatile organic compounds (SVOCs), and the presence of 4 genera of mold. Results show that the future indoor air quality does not only depend on the emissions of each building product but that it is also closely related to the whole implementation process. Mold spore measurements can reach 1400 CFU/m 3, which is particularly high compared with the concentrations usually measured in indoor environments. Relatively low concentrations of VOCs were observed, in relation to the use of low emissive materials. Among SVOCs analyzed, some phthalates, permethrin, and hydrocarbons were found in significant concentrations upon the delivery of building as well as triclosan, suspected to be endocrine disruptor, and yet prohibited in the treatment of materials and construction since 2014. As some regulations exist for VOC emissions, it is necessary to implement them for SVOCs due to their toxicity.